2019
DOI: 10.1007/s00277-019-03754-3
|View full text |Cite
|
Sign up to set email alerts
|

Ileostomy for steroid-resistant acute graft-versus-host disease of the gastrointestinal tract

Abstract: Steroid-resistant acute graft-versus-host disease (GVHD) of the gastrointestinal tract associates with important morbidity and mortality. While high-dose steroids are the established first-line therapy in GVHD, no second-line therapy is generally accepted. In this analysis of 65 consecutive patients with severe, steroid-resistant, intestinal GVHD (92% stage 4), additional ileostomy surgery significantly reduced overall mortality (hazard ratio 0.54; 95% confidence interval, 0.36-0.81; p = 0.003) compared to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Therefore, the mortality was mainly due to the complications of ASCT rather than the severity of the causal hematologic disease. Our results are consistent with the outcome of diverting ostomy in patients with a SR stage 4 GI-aGVHD reported for the first time by Turki and coworkers in 2019 33 . Their study included 10 patients (8 adults and 2 children) treated with ileostomy (n = 7), jejunostomy (n = 2), and loop ascendostomy (n = 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the mortality was mainly due to the complications of ASCT rather than the severity of the causal hematologic disease. Our results are consistent with the outcome of diverting ostomy in patients with a SR stage 4 GI-aGVHD reported for the first time by Turki and coworkers in 2019 33 . Their study included 10 patients (8 adults and 2 children) treated with ileostomy (n = 7), jejunostomy (n = 2), and loop ascendostomy (n = 1).…”
Section: Discussionsupporting
confidence: 91%
“…Considering these data, we hypothesized that a proximal diverting enterostomy (DE) would allow controlling severe steroid-refractory (SR) GI-aGVHD forms in the distal excluded ileocolonic segment. Recently, Turki and coworkers reported encouraging results of enterostomy in 10 patients experiencing stage 4 GI-aGVHD refractory to high-dose of corticosteroid 33 …”
mentioning
confidence: 99%
“…Although less significant, similar results were obtained for IL-4, especially in lamina propria lymphocytes (41). Another study also showed ileostomy-induced immune modulation with a > 50% decrease in activated T cell numbers and an increase in that of regulatory T cells in patients with steroid-resistant acute graft-versus-host disease of the gastrointestinal tract (42). Consistent with this, a lack of luminal stimulation reduces the contact between the immune barrier and foreign antigens, which weakens the ability of the adaptive immunity.…”
Section: Changes In the Intestinal Mucosal Barriermentioning
confidence: 55%
“…Conventional GVHD treatment and antiviral treatment were considered inadequate for further therapy, and the obliterating character of the inflammatory process was of such a nature that surgery was considered as the best therapeutic option. Surgical intervention for intestinal GVHD or other post-allo-HSCT complications is rarely necessary, and only a few cases and minor patient material are reported regarding this treatment approach [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%